PERTUMBUHAN SEMAI KELOR (Moringa oleifera) ASAL NUSA TENGGARA TIMUR DENGAN PERLAKUAN PERBEDAAN MEDIA TUMBUH - Kurniawan, Hery (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
Kelor is a plant species that has many benefits because of its nutritional content. The World Health Organization (WHO) has declared Moringa as a miracle plant, because it has saved many lives, especially children in many poor countries. Kelor has the opportunity to be developed in Sumatra, especially Riau as an alternative food crop, source of some important nutrients such as vitamins, proteins and anti-oxidants. Kelor from East Nusa Tenggara (NTT) is known to have the best quality in Indonesia. Its development in Riau requires preliminary research related to the growth of seedlings in several growing medium that have characteristics similar to those in Riau. This study uses a completely randomized design with treatment of growing medium in the form of three treatments, namely black soil, podsolic soil and peat soil mixture. The analysis was carried out descriptively and inference to the parameters of the percentage of life and height of Moringa seedlings. The results showed that seedling growing medium from top soil + fuel husk were best for Moringa seedling growth. Seedling growing media from top soil sub soil or from top soil alone can be the best alternative afterwards.